Electrical and transport properties of nearly stoichiometric transparent n‐type silver indium oxide thin films. Issue 11 (1st September 2016) - Keerthi, K.; Tarachand, P.; Okram, G. S.; Shripathi, T.; Ganesan, V.; Nair, B. G.; Abraham, A.; Philip, R. R.
Abstract : The possibility of combining both optical transparency and high electrical conductivity in the same material makes transparent conducting oxides one of the most sought after materials in transparent electronics. This paper presents the investigations done on the conductivity mechanisms of n‐type transparent conducting silver indium oxide thin films in different temperature ranges varying from 6 to 333 K. X‐ray diffraction indicates the films to be amorphous, and the morphology of the films from scanning electron microscopy and atomic force microscopy shows agglomerations with average particle size ∼30 nm. X‐ray photoelectron spectroscopy and energy‐dispersive analysis of X‐rays establish the films to be nearly stoichiometric with In/Ag at.% ratio in the range 1.1–1.2. The transmittance percentage obtained from optical transmittance and absorbance spectra is moderately high and the bandgap energy of the thin films is ∼3.5 eV. Transport parameters, such as carrier mobility ∼10 3  cm 2 /V s and carrier concentration ∼10 18 /cm 3, are elucidated from Hall and thermopower data.